Is the Multidimensional Poverty Index robust to different weights? - Alkire, S; Santos, M; Seth, S; Yalonetzky, G (Oxford Poverty & Human Development Initiative (OPHI), 2010)
This paper presents the results of robustness tests, which show that the Multidimensional Poverty Index, developed by OPHI for the UNDP Human Development Report, is robust to a range of different weights.